“What Kind of Migrant Are You?”—Iranian Migrants in the West, Racial Complexity and Myths of Belonging - Shima Shahbazi (Genealogy)
In this article, I analyse the complexity of the status of “migrant” in relation to myths of belonging and what we call “home”. I look at status labels that Iranian border-crossers embrace after migrating to the Global North and the ways in which they practice adaptability in accordance with the systemic and structural meanings associated with their migration status and their racial complexity. Ethnic and Racial labels adopted by Iranian migrants can include “Persian”, “Iranian”, “Middle Eastern”, “White”, or “Aryan”, and migration status labels range from “migrant” to “refugees and asylum seekers”, “exiles”, “expats” etc. Using a mixed approach of digital ethnographies, autoethnography and textual analysis, together with an intersectional and decolonial lens, I investigate the ways in which migration status such as skilled categories are associated with not only “fitting” into the neoliberal and capitalist systems of border crossing but also “blending” into racial hierarchies and maintaining class status post migration within White contexts. This article takes an empathetic approach to the lived experiences of minority and racially complex migrants and emphasises the epistemic value of their narratives and the ways in which these stories can inform us about the covert systemic structural and racially loaded bias that exists within migration economies of the Global North.